Hematocrit and 28-day mortality in mechanically ventilated septic patients: a prospective observational study - Lianghai Cao; Youlian Zhou; Pengcheng Shen; Hui Cui; Jin Tang; Min Xiao; Ping Fang; Guilan Ding; Jun Qiu (Frontiers in Medicine, 2026)
Background Sepsis is a condition that can lead to severe complications and is estimated to affect 300 million people annually. Patients requiring mechanical ventilation represent a particularly critical subgroup with high mortality. While hematocrit (HCT) has been identified as a prognostic marker in general sepsis populations, its specific role in mechanically ventilated patients remains unexplored. The objective of this study is to examine the relationship between HCT levels and 28-day mortality in this vulnerable patient cohort. Methods In this prospective observational study, an exploratory candidate cutoff for HCT was empirically derived by maximizing the Youden index from the ROC curve to predict 28-day mortality. The cohort was then stratified into low-HCT and high-HCT groups, utilizing the aforementioned candidate threshold. To assess the stability of this data-driven cutoff, an internal bootstrap validation procedure was performed. Subsequently, the association between HCT stratification and 28-day mortality was evaluated using a Cox proportional hazards regression model, adjusting for prespecified covariates. Results Among the 233 patients included in the study, 40 (17.2%) died within 28 days. Patients were stratified into two groups, low HCT (<26.65%) and high HCT (≥26.65%), based on the exploratory HCT cutoff of 26.65%. In the multivariable Cox proportional hazards model, patients in the low HCT group exhibited a significantly elevated risk of 28-day mortality compared to those in the high HCT group (adjusted hazard ratio [HR] = 2.16, 95% CI: 1.04–4.52; p < 0.05). Conclusion In this multicenter study, an exploratory HCT cutoff of 26.65% was identified, and it was observed that low HCT was associated with a 2.16-fold increased risk of 28-day mortality in mechanically ventilated sepsis patients. However, the discriminative ability of HCT was modest (AUC ≈ 0.537), suggesting limited predictive utility as a standalone test. Given its low cost and routine availability, HCT may still hold value as an adjunctive variable in risk stratification. However, further investigation is necessary to validate its incremental prognostic value and determine its optimal integration with other established predictors in larger, well-powered cohorts.